Losing your head : abjection, aesthetic conflict, and psychoanalytic criticism - Civitarese, Giuseppe, 1958- (Rowman and Littlefield, 2015)
Losing Your Head looks at the subject of beheading in art as a trope of the destruction of the mind. It focuses on new psychoanalytic tools that aid in understanding how a mind is born and grows, as well as what art can teach psychoanalysts about their work.